Boosting Job Growth in the Western Balkans - Kovtun, Dmitriy (IMF Working Papers; Working Paper, 2014)
Labor markets in the Western Balkan countries (Albania, Bosnia and Herzegovina, Kosovo, Macedonia, Montenegro, and Serbia) are characterized by some of the highest unemployment and low employment rates in Europe. We analyze the poor labor market outcomes in these countries by comparison with the New Member States of the European Union and advanced European economies. Our findings suggest that long-lasting labor market weaknesses in the Western Balkans have structural roots: the institutional setup of the labor markets, labor cost factors, and especially the unfinished transition process. Finally, we offer policy recommendations for boosting job creation.